Pandemic 2009 influenza A (H1N1)‐associated deaths among children in China: A retrospective analysis - Zhiwei Lu; Yuejie Zheng; Yanxia He; Huizhong Chen; Heping Wang; Ling Cao; Deyu Zhao; Wei Ji; Yunxiao Shang; Changchong Li; Zhimin Chen; Shunying Zhao; et al. (Wiley, 2018)
Abstract Importance A cluster of influenza‐associated deaths occurred among children during pandemic 2009 influenza A (H1N1) in China, but the risk factors and causes for death have not been clarified. Objective We describe the clinical findings regarding 2009 influenza A (H1N1)‐associated pediatric deaths in China, including the risk factors for death. Methods The definition of 2009 influenza A (H1N1)‐associated pediatric death is death in a child who is younger than 14 years and has laboratory‐confirmed influenza. We collected data of total 810 hospitalized patients with 2009 influenza A (H1N1) infection from September 2009 to February 2010 in 17 hospitals across China. The clinical characteristics, laboratory abnormalities, and treatment course were retrospectively studied. Results Of the 810 patients hospitalized with 2009 influenza A (H1N1) infection, 19 (2.3%) died. Ten patients died from severe pneumonia and acute respiratory distress syndrome; eight died from encephalopathy/encephalitis; one died from secondary fungal meningitis. Patients who died were more likely than patients who survived to have neutrophilia, lymphopenia, elevated C‐reactive protein, and elevations of lactate dehydrogenase, creatine kinase, creatine kinase‐MB, aspartate aminotransferase and alanine aminotransferase. There were no significant differences in the median age, median time from onset of illness to admission, underlying chronic disease, and initiation of antiviral therapy within 48 hours of illness onset, between patients who died and those who survived. Interpretation The risk factors for pediatric death associated with 2009 influenza A (H1N1) infection are different from those of seasonal influenza. The most common causes of death are viral pneumonia, acute respiratory distress syndrome, and encephalopathy/encephalitis.